Deployment of intrusion detection nodes to prevent wormhole attacks in Mobile Ad hoc Networks. (24th June 2011) - Su, Ming-Yang
This study proposes an approach to deploy a node implementing Intrusion Detection System (IDS) in MANETs for detecting and isolating wormhole nodes, if they exist. All IDS nodes must be set in sniffing mode to execute a mechanism called Anti-Wormhole Mechanism (AWM). An IDS node will broadcast a block message to all nodes within its communication range when a neighbouring node's suspicious value exceeds the threshold. This study uses ns2 to evaluate the proposed IDS nodes, and the results show that these IDSs can rapidly and correctly block the wormhole nodes under the circumstances of low false positives.